CO2 capture performance of calcium-based synthetic sorbent with hollow core-shell structure under calcium looping conditions - Ma, Xiaotong; Li, Yingjie; Duan, Lunbo; Anthony, Edward J.; Liu, Hantao (Elsevier, 2018)
A novel calcium-based synthetic CO2 sorbent with hollow core-shell structure was prepared by a carbon microsphere template route where carbide slag, alumina cement and glucose were employed as the low-cost calcium precursor, support and carbon source, respectively. The effects of the alumina cement addition, the pre-calcination temperature during the preparation process, the carbon template addition and calcination conditions on CO2 capture performances of the calcium-based synthetic sorbents were studied during calcium looping cycles. The synthetic sorbent containing 5 wt.% alumina cement possesses the highest CO2 capture capacity during calcium looping cycles, which is mainly composed of CaO and Ca12Al14O33. The CO2 capture capacities of the synthetic sorbent under mild and severe calcination conditions can retain 0.37 and 0.29 g/g after 20 cycles, which are 57% and 99% higher than those of carbide slag under the same conditions, respectively. The synthetic sorbent possesses a hollow micro-sphere morphology with a nano-structured shell and meso-porous structure, which decreases the diffusion resistance of CO2. Periodic density functional theory (DFT) calculations are used to explain why Ca12Al14O33 can effectively retard both agglomeration and sintering of the synthetic sorbent. The hollow core-shell model is proposed to explain the CO2 capture mechanism of the synthetic sorbent. For the same CO2 capture efficiency, the energy consumption in the calciner using the synthetic sorbent is much lower than those using carbide slag and natural limestone. This work designs a good method to prepare the hollow sphere-structured synthetic sorbents with high CO2 capture capacity and provides a promising way to integrate efficient CO2 capture with the utilization of industrial waste.
Keywords: Carbide slag; Carbon template; Hydrothermal carbonization; Calcium looping; CO2 capture